Development of a translational model to screen medications for cocaine use disorder II: Choice between intravenous cocaine and money in humans. (1st August 2016) - Lile, Joshua A.; Stoops, William W.; Rush, Craig R.; Negus, S. Stevens; Glaser, Paul E.A.; Hatton, Kevin W.; Hays, Lon R.
Highlights: Animal-to-human translation in addiction research has lacked coordination. We developed homologous choice procedures in monkeys and humans. In humans, choice behavior was a systematic function of cocaine dose and money value. Choice behavior in humans and monkeys was functionally equivalent. This platform will be useful for screening cocaine use disorder medications. Abstract: Background: A medication for treating cocaine use disorder has yet to be approved. Laboratory-based evaluation of candidate medications in animals and humans is a valuable means to demonstrate safety, tolerability and initial efficacy of potential medications. However, animal-to-human translation has been hampered by a lack of coordination. Therefore, we designed homologous cocaine self-administration studies in rhesus monkeys (see companion article) and human subjects in an attempt to develop linked, functionally equivalent procedures for research on candidate medications for cocaine use disorder. Methods: Eight (N = 8) subjects with cocaine use disorder completed 12 experimental sessions in which they responded to receive money ($0.01, $1.00 and $3.00) or intravenous cocaine (0, 3, 10 and 30 mg/70 kg) under independent, concurrent progressive-ratio schedules. Prior to the completion of 9 choice trials, subjects sampled the cocaine dose available during that session and were informed of the monetary alternative value. Results: The allocation of behavior varied systematically as a function of cocaine dose and money value. Moreover, a similar pattern of cocaine choice was demonstrated in rhesus monkeys and humans across different cocaine doses and magnitudes of the species-specific alternative reinforcers. The subjective and cardiovascular responses to IV cocaine were an orderly function of dose, although heart rate and blood pressure remained within safe limits. Conclusions: These coordinated studies successfully established drug versus non-drug choice procedures in humans and rhesus monkeys that yielded similar cocaine choice behavior across species. This translational research platform will be used in future research to enhance the efficiency of developing interventions to reduce cocaine use.